2008
DOI: 10.1002/joc.1715
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of near‐surface diurnal temperature variations and trends in southern Mexico

Abstract: ABSTRACT:We assembled daily maximum temperature, minimum temperature and precipitation records for 143 stations in southern Mexico over the period . We found that the average temperature for the region has increased linearly at a rate of 0.086°C per decade with maximum temperatures increasing at twice that rate and minimum temperatures basically remaining unchanged. This results in a highly statistically significant increase in the diurnal temperature range of 0.160°C per decade. We found that the variations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 28 publications
1
10
0
1
Order By: Relevance
“…Observed warming trends are known to have been stronger at night than during the day (e.g., Easterling et al 1997Easterling et al , 2000b resulting in a decreased diurnal temperature range. Stronger nighttime heating trends have been observed at many locations around the globe and, in spite of modeling inconsistencies ) and recent observations that trends in diurnal temperature range may have ceased globally (Trenberth et al 2007) or may be increasing over some regions (e.g., southern Mexico;Peralta-Hernandez et al 2008), warmer nights are among the most widespread expectations from anthropogenic global climate change (e.g., Tebaldi et al 2006). In this regard, the California region has been meeting expectations.…”
Section: Introductionmentioning
confidence: 99%
“…Observed warming trends are known to have been stronger at night than during the day (e.g., Easterling et al 1997Easterling et al , 2000b resulting in a decreased diurnal temperature range. Stronger nighttime heating trends have been observed at many locations around the globe and, in spite of modeling inconsistencies ) and recent observations that trends in diurnal temperature range may have ceased globally (Trenberth et al 2007) or may be increasing over some regions (e.g., southern Mexico;Peralta-Hernandez et al 2008), warmer nights are among the most widespread expectations from anthropogenic global climate change (e.g., Tebaldi et al 2006). In this regard, the California region has been meeting expectations.…”
Section: Introductionmentioning
confidence: 99%
“…The probable effect of this process in adjacent regional extent deserves further research [42]. On the other hand, 43 stations developed increasing TR trends, from these, 26 had larger TMaxAvg slope values, a similar result described by [43] in Spain and for Mexico by [20] [21] [44]. The mechanisms of this process is described by [2] who posed that the conversion of soil cover increase TR due to the decrease of evaporative cooling, consequently increasing TMaxAvg in daytime, when evaporation and maximum temperature occur, a very evident process in semi-arid and seasonal regions.…”
Section: Annual Trendsmentioning
confidence: 83%
“…The mechanisms for these effects have been demonstrated by modeling programs [49]- [51] among many others that have depicted the reduced evapotranspiration as a main cause of warming as a consequence of deforestation in seasonal and arid zones as the one here analyzed. The conversion of natural forest into agricultural fields and its warming effect has been also widely documented by field evidence at different spatial scales [44] [52] [53]. In the North Pacific Watershed, specifically in Sinaloa the transformation of original vegetation into agricultural land has been taking place since the decade of the 20s in the past century, increasing its pace in the mid 50s and early 60s with the construction of river dams and irrigation channels, mainly in the middle and northern regions, where are found 88% of the total irrigated are in the region, decimating essentially the vegetation of the CP [54].…”
Section: Discussionmentioning
confidence: 98%
“…Studies made by Peralta-Hernández et al (2009) in southeastern Mexico, showed significant trend in the increase of the maximum temperatures in the region, as well as in the frequency of warm days. Despite the importance of this issue, there is no information on trends from climate change in indices in the state of Chiapas.…”
Section: Introductionmentioning
confidence: 96%
“…Estudios realizados por Peralta-Hernández et al (2009) en el sureste de México, mostraron tendencia significativa en el incremento de las temperaturas máximas en la región, así como en la frecuencia de días cálidos. A pesar de la importancia de esta temática, no existe información sobre las tendencias de los índices de cambio climático en el estado de Chiapas.…”
Section: Introductionunclassified